The Counselor Feedback Training Model: Teaching Counseling Students Feedback Skills. Issue 2 (3rd October 2013) - Swank, Jacqueline M.; McCarthy, Shannon N.
<x xml:space="preserve">Abstract</x> Giving and receiving feedback is an important counseling skill; therefore, it is crucial to focus on this skill within counselor training. This article presents the Counselor Feedback Training Model, a developmental approach designed to assist counselor educators in teaching counseling students how to give and receive feedback.